Introduction to the Theme Issue: Christian Perspectives on The City - Toly, Noah (Christian scholar's review, 2009)
Sometime in 2008, most demographers would agree, we crossed a historic threshold, one that is meaningful to Christian scholarship. Until then, and since the earliest days of civilization, the bulk of the world’s population lived in rural areas. Even at the turn of the 20th century, only 10% of the world’s population lived in cities.